PENCEGAHAN PENYEBARAN INFEKSI DAN PENGGUNAAN TELEDENTISTRY SELAMA PANDEMI COVID-19 - Nyoman Ayu Anggayanti; Putu Lestari Sudirman; Putu Fenti Surya Pratami; Dewi Anggraini (Universitas Baiturrahmah, 2021)
Introduction: COVID-19 is a new virus that was first discovered in Wuhan, China. In mid-2020, the number of deaths continued to increase worldwide. Topics: Dentist are professions that are susceptible to infection, so they must implement preventive measures and apply alert behavior to all patients. Discussion: The American Dental Association (ADA) describes teledentistry as